Pengembangan Multimedia Interaktif Berbasis Representasi Kimia untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Larutan Penyangga. - Nabiela Nailul Amalia; Sukarmin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Buffer solutions are one of the most challenging topics in chemistry because they require students to simultaneously connect macroscopic phenomena, submicroscopic processes, and symbolic representations. This difficulty results in low levels of conceptual understanding and learning outcomes among students. This study aims to develop an interactive multimedia tool based on chemical representations specifically, the “Buffer Chemistry” application and to assess its suitability for teaching buffer solutions. The study employed the Research and Development (R&D) method using the 4D model, limited to the “develop” stage. A limited pilot test was conducted with 36 11th-grade students at SMA Negeri 5 Surabaya using a one-group pretest-posttest design. Data were collected through expert validation sheets, student response questionnaires, activity observations, and learning outcome tests. The results showed that the multimedia achieved a median score of 5 in the aspects of content and construct validity, falling into the “very good” category. The practicality of the media was demonstrated by a student response rate of 92.86% and a rate of relevant learning activities of 98.32%. The effectiveness of the multimedia was evident from the increase in students’ average scores from 56.11 to 89.72, supported by the results of the Wilcoxon test, which showed a significant difference between the pretest and posttest (p < 0.001), as well as an average N-Gain of 0.768 in the high category. The results of the study indicate that “Buffer Chemistry” is suitable for use as a teaching tool that helps students understand the concept of buffer solutions more thoroughly and improves their learning outcomes.